Satisfaction with treatment of atopic dermatitis in children - Maciejewska-Franczak, Małgorzata; Majak, Paweł; Kaczmarek, Jadwiga; Antczak, Adam (Dermatology Review/Przegląd Dermatologiczny, 2016)
Introduction . Atopic dermatitis is a frequent chronic skin disease in children. The major clinical manifestations include itching and dryness of the skin. The pathomechanism of skin changes results from an interaction of genetic and environmental factors as well as impairments of skin barrier function and immune response. Despite chronic treatment the disease is characterized by exacerbation and remission periods and lowers the quality of life of patients and their families. Objective. To evaluate treatment satisfaction in children with atopic dermatitis, identify components of medical care which contribute to treatment satisfaction, and evaluate the relationship between satisfaction and adherence to a doctor’s recommendations. Material and methods. One hundred and nineteen children (6 months to 12 years old, mean age 4.9 years) with atopic dermatitis were enrolled in the study. The doctor performed physical examinations and history taking and filled in questionnaires evaluating the course and exacerbation of the disease, the type of administered therapy and diagnostics. The patients’ parents completed two questionnaires: a questionnaire assessing satisfaction with the therapy (the type of recommended therapy, adherence to recommendations, contact with the doctor, obtained information, degree of psychological support, role of parents in taking decisions regarding the therapy) and a quality of life questionnaire. Results. The authors observed that 56% of parents were dissatisfied with the administered treatment, and 40% failed to adhere to at least one therapeutic recommendation. Parents of children with mild atopic dermatitis significantly more often stop using emollients. It was also observed that lack of treatment satisfaction in children with severe atopic dermatitis whose parents are insufficiently educated contributes to decreased adherence. The authors identified independent factors of lack of treatment satisfaction: failure to obtain enough psychological support (OR = 20.00), failure to obtain reliable information on the disease (OR = 5.91), failure to actively get engaged in the treatment procedure (OR = 5.31), dissatisfaction with the contact with the doctor (OR = 4.9), dissatisfaction with the diagnostics (OR = 4.93) and severe course of the disease (OR = 2.82). Conclusions . Elimination of risk factors of dissatisfaction with the treatment might potentially improve the adherence to chronic treatment in atopic dermatitis.